Theoretical and computational acoustics 2003 : Honolulu, Hawaii, 11-15 August 2003 - Tolstoy, Alexandra, Dr; Teng, Yu-Chiung; Shang, Erchang (World Scientific, 2003)
The ICTCA conference provides an interdisciplinary forum for active researchers in academia and industry who are of varying backgrounds to discuss the state-of-the-art developments and results in theoretical and computational acoustics and related topics. The papers presented at the meeting cover acoustical problems of common interest across disciplines and their accurate mathematical and numerical modeling. This volume collects papers that were presented at the sixth meeting. The subjects include geophysics, scattering and diffraction, the parabolic equation (with special sessions in honor of.